2010
DOI: 10.1039/c000664e
|View full text |Cite
|
Sign up to set email alerts
|

The gas-phase structure of octaphenyloctasilsesquioxane Si8O12Ph8 and the crystal structures of Si8O12(p-tolyl)8 and Si8O12(p-ClCH2C6H4)8

Abstract: The equilibrium molecular structure of octaphenyloctasilsesquioxane Si(8)O(12)Ph(8) in the gas phase has been determined by electron diffraction. It was found to have D(4) point-group symmetry, with Si-O bond lengths of 1.634(15)-1.645(19) A, and a narrow range [147.5(45)-149.8(24) degrees] of Si-O-Si angles. The structures of Si(8)O(12)(p-tolyl)(8) and Si(8)O(12)(p-ClCH(2)C(6)H(4))(8) have been determined by X-ray diffraction and are found to have Si(8)O(12) cages significantly distorted from the symmetry fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…It is a typical approach for large and flexible molecules successfully used in studies. [32,44,45] Secondly, anharmonic corrections computed from the molecular dynamics trajectories [29,30] (k MD ) were applied. We also calculated third derivatives for the major conformer at the B3LYP/6-31++G** level and computed the anharmonic vibrational corrections by using SHRINK (k 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is a typical approach for large and flexible molecules successfully used in studies. [32,44,45] Secondly, anharmonic corrections computed from the molecular dynamics trajectories [29,30] (k MD ) were applied. We also calculated third derivatives for the major conformer at the B3LYP/6-31++G** level and computed the anharmonic vibrational corrections by using SHRINK (k 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…The present study is another indication (together with our previous works [13,16,40]) that gas-phase electron diffraction method, combined with DFT computations, can be successfully applied in direct structural characterizations of fairly large (100 atoms and more) molecules. Moreover, the accuracy achieved in this investigation shows that 137 atoms is definitely not an upper limit, especially for highly symmetric molecules.…”
Section: Discussionmentioning
confidence: 70%
“…The rectilinear approach, when applied to molecules with one or more low frequency (less than about 50 cm À1 ) vibrational modes, tends to produce vibrational corrections for bonded distances that are unreasonably large [39]. The curvilinear approach is generally considered more realistic and physically appealing; recently it has been successfully applied in several studies of large macroheterocyclic molecules [13,14,[16][17][18]40] and may be considered the present state-of-the-art for large molecules. In the present study a refinement with k h1 corrections calculated from the B3LYP/ cc-pVTZ computation was used.…”
Section: Methodsmentioning
confidence: 97%
“…1), but only a few previous studies have described cage molecules containing 4, 6, 10, or 12 silsesquioxane fragments. By contrast, over 1000 previous studies have reported octameric cage molecules [RSiO 1.5 ] 8 (cubic structures) with different organic groups at the silicon atom [2,[11][12][13][14][15][16][17][18][19][20][21][22] (see Table 1). M a n u s c r i p t 3 This prevalence of octameric structures among structures with the same composition but different sizes is not accidental, and there are several possible explanations.…”
Section: Introduction Of Metal Atoms Into Cage Siloxane Structurementioning
confidence: 70%
“…26) obtained by reacting various organotrimethoxysilanes RSi(OMe) 3 with different Р-containing alkali metal wolframates (e.g., K 7 [PW 11 O 39 ]·13H 2 O) in an acidic aqueous medium comprise a distinct group of compounds. The anions of polywolframic and polywolframate phosphoric acids belong to a huge class of heteropolyoxometalates, which are used as sorbents and ion exchange systems in micro-and nano-electronic devices, as well as in electrochemical sensors [102,103].…”
Section: [101]mentioning
confidence: 99%